Educational Data Mining on Student Academic Performance Prediction: A Survey: Educational Data Mining Pada Prediksi Kinerja Akademik Mahasiswa : Sebuah Survey - Indahyanti, Uce; Azizah, Nuril Lutvi; Setiawan, Hamzah (Procedia of Social Sciences and Humanities, 2022)
Student academic performance prediction has become a hot research topic, and is still a research trend in the field of educational data mining (EDM). The application of data mining in the education domain can find some hidden knowledge and patterns, which help in decision making for management to improve the education system. This study presents survey results in the form of systematic mapping of literature related to EDM, which aims to identify methods, datasets, and results obtained by researchers in the last five years.